Ti2C-coated MoS2 composite material as well as preparation method and application thereof

By preparing Ti2C@MoS2 composite material, the heterostructure and excellent piezoelectric effect are used to significantly improve catalytic activity and stability, solving the problem of low hydrogen production efficiency of existing catalysts, and achieving efficient piezoelectric catalytic water decomposition and hydrogen production.

CN119838618APending Publication Date: 2025-04-18QUANZHOU NORMAL UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510075139.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the existing piezoelectric catalytic water decomposition hydrogen production technology, the catalytic performance and stability of the catalyst still need to be improved, resulting in low hydrogen production efficiency.

Method used

By mixing the molybdenum source, sulfur source and Ti2C for reduction reaction, a Ti2C@MoS2 composite material was prepared to form a heterostructure and utilize its excellent piezoelectric effect to significantly improve the catalytic activity and stability of molybdenum disulfide.

Benefits of technology

When piezoelectric catalytic water decomposition is used to produce hydrogen, the Ti2C@MoS2 composite material exhibits excellent hydrogen production rate and good cycle stability, and the hydrogen production rate can reach 870.09μmol·g-1·h-1.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838618A_ABST
    Figure CN119838618A_ABST
Patent Text Reader

Abstract

The invention provides a Ti2C-coated MoS2 composite material as well as a preparation method and application thereof, and belongs to the technical field of catalytic hydrogen production. The preparation method comprises the following steps: mixing a molybdenum source, a sulfur source, an organic solvent and Ti2C, and reducing under a high-temperature condition to obtain the Ti2C-coated MoS2 composite material. Ti2C and MoS2 are combined to form a heterostructure through a high-temperature reduction reaction, the excellent piezoelectric effect of the heterostructure is utilized, the catalytic activity and stability of molybdenum disulfide are remarkably improved, and the excellent hydrogen production rate is achieved when hydrogen is produced through piezoelectric catalysis of water decomposition. The result of the embodiment shows that the hydrogen production rate of the Ti2C-coated MoS2 composite material prepared by the preparation method disclosed by the invention can reach 870.09 [mu] mol.g <-1 >. H <-1 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalytic hydrogen production, and specifically relates to a Ti2C@MoS2 composite material and a preparation method and application thereof. Background Art

[0002] With the aggravation of energy crisis and environmental pollution problems, hydrogen has attracted widespread attention as a clean and efficient energy carrier. Hydrogen production by water splitting mainly includes electrocatalytic water splitting and piezoelectric water splitting. Among them, electrocatalytic water splitting has high energy consumption, while piezoelectric water splitting can convert a wide range of low-frequency mechanical energy into chemical energy with low energy consumption, and has gradually become an ideal method for hydrogen production. In the process of piezoelectric water splitting, the selection of catalysts is crucial. Molybdenum disulfide is a typical transition metal sulfide compound and a commonly used catalyst in the prior art. However, its catalytic performance still needs to be further improved. Summary of the invention

[0003] The object of the present invention is to provide a Ti2C@MoS2 composite material and a preparation method and application thereof. The Ti2C@MoS2 composite material prepared by the preparation method provided by the present invention has excellent hydrogen production efficiency when producing hydrogen by piezoelectric catalytic water decomposition.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing a Ti2C@MoS2 composite material, comprising:

[0006] A molybdenum source, a sulfur source, an organic solvent and Ti2C are mixed and subjected to a reduction reaction to obtain a Ti2C@MoS2 composite material; the temperature of the reduction reaction is 200-280°C.

[0007] Preferably, the molybdenum source includes molybdenum acetylacetonate, sodium molybdate or ammonium molybdate.

[0008] Preferably, the sulfur source includes dodecanethiol, sulfur powder, thiourea, thioacetamide or L-cysteine.

[0009] Preferably, the organic solvent is 1-octadecene.

[0010] Preferably, the mass ratio of the molybdenum source, the sulfur source and the organic solvent is 1:(1.5-2.5):(0.5-1.5).

[0011] Preferably, the reduction reaction time is 2 to 6 hours.

[0012] Preferably, the molar ratio of Ti2C and MoS2 in the Ti2C@MoS2 composite material is 1:(1-2).

[0013] The present invention also provides a Ti2C@MoS2 composite material prepared by the preparation method described in the above technical solution, comprising Ti2C and MoS2 loaded on the surface of the Ti2C.

[0014] The present invention also provides the application of the Ti2C@MoS2 composite material described in the above technical solution in piezoelectric catalytic water decomposition to produce hydrogen.

[0015] Preferably, the mass ratio of the Ti2C@MoS2 composite material to the volume of water is 5 mg: (5-15) mL.

[0016] The present invention provides a method for preparing a Ti2C@MoS2 composite material, comprising: mixing a molybdenum source, a sulfur source, an organic solvent and Ti2C, and performing a reduction reaction to obtain a Ti2C@MoS2 composite material; the temperature of the reduction reaction is 200 to 280°C. The present invention combines Ti2C and MoS2 to form a heterostructure through a high-temperature reduction reaction, and utilizes its excellent piezoelectric effect to significantly improve the catalytic activity and stability of molybdenum disulfide, and has an excellent hydrogen production rate when piezoelectrically catalyzing water decomposition to produce hydrogen. The results of the embodiment show that the hydrogen production rate of the Ti2C@MoS2 composite material prepared by the present invention can reach 870.09μmol·g -1 ·h -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 XRD patterns of the Ti2C@MoS2 composite materials prepared in Examples 1 to 3, Ti2C in Comparative Example 1, and MoS2 in Comparative Example 2;

[0018] Figure 2 This is the SEM image of the Ti2C@MoS2 composite material prepared in Example 1;

[0019] Figure 3 The hydrogen production performance diagram of the Ti2C@MoS2 composite material prepared in Examples 1 to 3, the Ti2C in Comparative Example 1, the MoS2 in Comparative Example 2, and the Ti2C@MoS2 composite material prepared in Comparative Example 3;

[0020] Figure 4 This is the hydrogen production performance diagram of the Ti2C@MoS2 composite material prepared in Example 2 after 5 cycles. DETAILED DESCRIPTION

[0021] The present invention provides a method for preparing a Ti2C@MoS2 composite material, comprising:

[0022] A molybdenum source, a sulfur source, an organic solvent and Ti2C are mixed and subjected to a reduction reaction to obtain a Ti2C@MoS2 composite material; the temperature of the reduction reaction is 200-280°C.

[0023] Unless otherwise specified, the present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.

[0024] In the present invention, the molybdenum source preferably includes molybdenum acetylacetonate (Mo(acac)2), sodium molybdate or ammonium molybdate.

[0025] In the present invention, the sulfur source preferably includes dodecanethiol (DDT), sulfur powder, thiourea, thioacetamide or L-cysteine.

[0026] In the present invention, the organic solvent is preferably 1-octadecene (ODE).

[0027] In the present invention, the mass ratio of the molybdenum source, the sulfur source and the organic solvent is preferably 1: (1.5-2.5): (0.5-1.5), and more preferably 1: 2: 1. The present invention controls the mass ratio of the molybdenum source, the sulfur source and the organic solvent within the above range, so that the obtained molybdenum disulfide can be a single-layer structure to expose more active edge sites, thereby further improving the catalytic performance of the composite material.

[0028] In the present invention, the particle size of the Ti2C is preferably 10 to 20 μm.

[0029] In the present invention, the mass ratio of the molybdenum source to Ti2C is preferably 1:(0.3-0.9). The present invention controls the mass ratio of the molybdenum source to Ti2C within the above range, so that the molar ratio of Ti2C to MoS2 in the Ti2C@MoS2 composite material is 1:(1-2), thereby improving the catalytic performance of the composite material.

[0030] In the present invention, the mixing of the molybdenum source, the sulfur source, the organic solvent and Ti2C is preferably as follows: the molybdenum source, the sulfur source, the organic solvent and Ti2C are mixed and purged with nitrogen for 10 to 30 minutes under stirring conditions. The present invention has no special limitation on the stirring rate, and a stirring technical solution well known to those skilled in the art can be adopted. The present invention has no special limitation on the flow rate of the nitrogen, and it can be selected according to actual needs. The present invention uses nitrogen purging to discharge air to prevent the raw materials from reacting with oxygen in the air.

[0031] In the present invention, the temperature of the reduction reaction is 200-280°C, preferably 220-280°C, more preferably 240-280°C, and most preferably 260-280°C; the time of the reduction reaction is preferably 2-6h, more preferably 4-6h; the heating rate to the reduction reaction temperature is preferably 5°C / min; the reduction reaction is preferably carried out under nitrogen protection. The present invention controls the temperature and time of the reduction reaction within the above range, so that the generated molybdenum disulfide has a single-layer structure and is closely arranged on the Ti2C surface, further improving the catalytic performance of the composite material.

[0032] After the reduction reaction is completed, the present invention preferably cools the product of the reduction reaction to room temperature, then adds ethanol for a first centrifugation, adds chloroform for washing, and then sequentially performs a second centrifugation, drying and grinding to obtain a Ti2C@MoS2 composite material.

[0033] The present invention has no special limitation on the cooling operation, and any cooling technical solution well known to those skilled in the art may be used.

[0034] The present invention has no particular limitation on the amount of ethanol used, and the amount can be selected according to actual needs.

[0035] In the present invention, the number of chloroform washing is preferably 4 to 5 times. The present invention has no special limitation on the amount of chloroform used in each washing, and it can be selected according to actual needs.

[0036] In the present invention, the speed of the first centrifugation and the second centrifugation is preferably 5000-7000 rpm, more preferably 6000 rpm; the time of the first centrifugation and the second centrifugation is preferably 10-20 min.

[0037] In the present invention, the drying temperature is preferably 50 to 70° C.; the drying time is preferably 12 to 24 hours.

[0038] The present invention has no special limitation on the grinding operation, and the grinding technical scheme well known to those skilled in the art can be adopted.

[0039] In the present invention, the molar ratio of Ti2C and MoS2 in the Ti2C@MoS2 composite material is preferably 1:(1-2). The present invention controls the molar ratio of Ti2C and MoS2 in the Ti2C@MoS2 composite material within the above range, which can further improve the catalytic performance and stability of the composite material.

[0040] The present invention mixes a molybdenum source, a sulfur source, an organic solvent and Ti2C, performs a reduction reaction, and obtains a Ti2C@MoS2 composite material. Ti2C and MoS2 are combined to form a heterostructure, and the excellent piezoelectric effect is utilized to significantly improve the catalytic activity and stability of molybdenum disulfide. The amount of each raw material, reaction temperature, time and other parameters are controlled, so that the composite material has excellent hydrogen production efficiency when producing hydrogen by piezoelectric catalytic water decomposition.

[0041] The present invention also provides a Ti2C@MoS2 composite material prepared by the preparation method described in the above technical solution, comprising Ti2C and MoS2 loaded on the surface of the Ti2C.

[0042] The Ti2C@MoS2 composite material prepared by the present invention has excellent hydrogen production rate and good cycle stability when producing hydrogen by piezoelectric catalytic water decomposition.

[0043] The present invention also provides the application of the Ti2C@MoS2 composite material described in the above technical solution in piezoelectric catalytic water decomposition to produce hydrogen.

[0044] The present invention preferably mixes the Ti2C@MoS2 composite material with water, and catalyzes water decomposition under the action of ultrasound to obtain hydrogen.

[0045] In the present invention, the mass ratio of the Ti2C@MoS2 composite material to the volume ratio of water is preferably 5 mg: (5-15) mL, more preferably 5 mg: 10 mL. The present invention controls the mass ratio of the Ti2C@MoS2 composite material to the volume ratio of water within the above range, and has a better hydrogen production rate.

[0046] In the present invention, methanol is preferably added when the Ti2C@MoS2 composite material is mixed with water.

[0047] In the present invention, the volume ratio of methanol to water is preferably (0.5-1.5):10, more preferably 1:10. In the present invention, adding methanol and controlling its amount can further increase the hydrogen production rate.

[0048] In the present invention, the power of the ultrasound is preferably 120 to 300 W; the frequency of the ultrasound is preferably 40 to 80 kHz. The present invention excites the piezoelectric effect of the Ti2C@MoS2 composite material through ultrasound, thereby catalyzing the decomposition of water to generate hydrogen. The present invention controls the power and frequency of the ultrasound within the above range, which can further increase the hydrogen production rate.

[0049] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] Example 1

[0051] A preparation method of a Ti2C@MoS2 composite material: Mo(acac)2, DDT, 1-octadecene (ODE) and 0.025gTi2C (10-20μm, the mass ratio of Mo(acac)2 and Ti2C is 1:0.6) in a mass ratio of 1:2:1 are mixed in a 50mL three-necked flask, the mixed solution is purged with nitrogen for 20min under magnetic stirring, the mixed solution is heated to 280℃ at a heating rate of 5℃ / min under nitrogen protection and kept warm for 4h, the reaction is naturally cooled to room temperature after completion, ethanol is added, the liquid is poured into a centrifuge tube for centrifugation, the waste liquid is poured out, and then the product is washed and centrifuged 4 times with chloroform, and then dried at 60℃ in a vacuum drying oven and ground to obtain a Ti2C@MoS2 composite material, the molar ratio of Ti2C and MoS2 in the Ti2C@MoS2 composite material is 1:1, and is recorded as Ti2C@MoS2-1.

[0052] Example 2

[0053] A preparation method of a Ti2C@MoS2 composite material: Mo(acac)2, DDT, 1-octadecene (ODE) and 0.0125g Ti2C (10-20μm, the mass ratio of Mo(acac)2 and Ti2C is 1:0.3) in a mass ratio of 1:2:1 are mixed in a 50mL three-necked flask, the mixed solution is purged with nitrogen for 10 minutes under magnetic stirring, the mixed solution is heated to 280°C at a heating rate of 5°C / min under nitrogen protection and kept warm for 2h, the reaction is naturally cooled to room temperature after completion, ethanol is added, the liquid is poured into a centrifuge tube for centrifugation, the waste liquid is poured out, and then the product is washed and centrifuged 4 times with chloroform, and then dried at 60°C in a vacuum drying oven and ground to obtain a Ti2C@MoS2 composite material, the molar ratio of Ti2C and MoS2 in the Ti2C@MoS2 composite material is 2:1, and is recorded as Ti2C@MoS2-2.

[0054] Example 3

[0055] A preparation method of a Ti2C@MoS2 composite material: Mo(acac)2, DDT, 1-octadecene (ODE) and 0.050gTi2C (10-20μm, the mass ratio of Mo(acac)2 and Ti2C is 1:0.9) in a mass ratio of 1:2:1 are mixed in a 50mL three-necked flask, the mixed solution is purged with nitrogen for 30min under magnetic stirring, the mixed solution is heated to 280℃ at a heating rate of 5℃ / min under nitrogen protection and kept warm for 6h, the reaction is naturally cooled to room temperature after completion, ethanol is added, the liquid is poured into a centrifuge tube for centrifugation, the waste liquid is poured out, and then the product is washed and centrifuged 4 times with chloroform, and then dried at 60℃ in a vacuum drying oven and ground to obtain a Ti2C@MoS2 composite material, the molar ratio of Ti2C and MoS2 in the Ti2C@MoS2 composite material is 1:2, and is recorded as Ti2C@MoS2-3.

[0056] Comparative Example 1

[0057] Ti2C in Example 1.

[0058] Comparative Example 2

[0059] Ti2C in Example 1 is omitted, and other parameters are the same as those in Example 1 to obtain MoS2.

[0060] Comparative Example 3

[0061] The 1-octadecene in Example 1 was replaced by water, and the other parameters were the same as those in Example 1 to obtain a Ti2C@MoS2 composite material, which was recorded as Ti2C@MoS2-4.

[0062] The XRD patterns of the Ti2C@MoS2 composite materials prepared in Examples 1 to 3, the Ti2C in Comparative Example 1, and the MoS2 in Comparative Example 2 are shown in FIG. Figure 1 As shown. Figure 1 It can be seen that the XRD pattern of the Ti2C@MoS2 composite material shows clear characteristic peaks of MoS2.

[0063] The Ti2C@MoS2 composite material prepared in Example 1 was observed using a scanning electron microscope, and the obtained SEM image is as follows: Figure 2 As shown. Figure 2 It can be seen that the flake-like MoS2 grows vertically on multilayer Ti2C, which effectively alleviates the interconnection and aggregation problems between numerous MoS2 nanosheets, which is a significant improvement over pure MoS2.

[0064] Application Examples

[0065] 5 mg of the Ti2C@MoS2 composite material prepared in Examples 1 to 3, the Ti2C in Comparative Example 1, the MoS2 in Comparative Example 2, and the Ti2C@MoS2 composite material prepared in Comparative Example 3 were mixed with 10 mL of water and 1 mL of methanol, and the piezoelectric effect was excited by ultrasound at a frequency of 45 kHz and a power of 300 W to catalyze water decomposition to produce hydrogen.

[0066] The hydrogen production performance of the Ti2C@MoS2 composite materials prepared in Examples 1 to 3, the Ti2C in Comparative Example 1, the MoS2 in Comparative Example 2 and the Ti2C@MoS2 composite materials prepared in Comparative Example 3 are as follows: Figure 3 As shown. Figure 3 It can be seen that the Ti2C@MoS2 composite material prepared in Example 2 has a better hydrogen production rate, which is 870.09 μmol·g -1 ·h -1 .

[0067] Under the same conditions, the hydrogen production performance of the Ti2C@MoS2 composite material prepared in Example 2 was tested 5 times in a cycle. The results are as follows: Figure 4 As shown. Figure 4 It can be seen that the Ti2C@MoS2 composite material prepared in Example 2 has good cycle stability after 5 cycles.

[0068] In summary, the Ti2C@MoS2 composite material prepared by the present invention has excellent catalytic performance and stability.

[0069] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a Ti2C@MoS2 composite material, comprising: A molybdenum source, a sulfur source, an organic solvent and Ti2C are mixed and subjected to a reduction reaction to obtain a Ti2C@MoS2 composite material; the temperature of the reduction reaction is 200-280°C.

2. The preparation method according to claim 1, characterized in that: The molybdenum source includes molybdenum acetylacetonate, sodium molybdate or ammonium molybdate.

3. The preparation method according to claim 1, characterized in that: The sulfur source includes dodecanethiol, sulfur powder, thiourea, thioacetamide or L-cysteine.

4. The preparation method according to claim 1, characterized in that: The organic solvent is 1-octadecene.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the molybdenum source, the sulfur source and the organic solvent is 1:(1.5-2.5):(0.5-1.5).

6. The preparation method according to claim 1, characterized in that: The reduction reaction time is 2 to 6 hours.

7. The preparation method according to claim 1, characterized in that: The molar ratio of Ti2C and MoS2 in the Ti2C@MoS2 composite material is 1:(1-2).

8. The Ti2C@MoS2 composite material prepared by the preparation method according to any one of claims 1 to 7, comprising Ti2C and MoS2 supported on the surface of the Ti2C.

9. Use of the Ti2C@MoS2 composite material according to claim 8 in piezoelectric catalytic water decomposition to produce hydrogen.

10. The use according to claim 9, characterized in that: The mass ratio of the Ti2C@MoS2 composite material to the volume of water is 5 mg: (5-15) mL.

Citation Information

Cited By

  • Selenium-doped layered mixed-phase molybdenum disulfide-based piezoelectric catalyst, preparation method and application

    CN121513909A